British military and naval medicine, 1600-1830 - Hudson, Geoffrey L. (Clio medica (Amsterdam, Netherlands), 2007)
Annotation Standing armies and navies brought with them military medical establishments, shifting the focus of disease management from individuals to groups. Prevention, discipline, and surveillance produced results, and career opportunities for physicians and surgeons. All these developments had an impact on medicine and society, and were in turn influenced by them. The essays within examine these phenomena, exploring the imperial context, nursing and medicine in Britain, naval medicine, as well as the relationship between medicine, the state and society. British Military and Naval Medicine challenges the notion that military medicine was, in all respects, 'a good thing?. The so-called monopoly of military medicine and the authoritarian structures within the military were complex and, at times, successfully contested. Sometimes changes were imposed that cannot be characterised as improvements. British Military and Naval Medicine also points to opportunities for further research in this exciting field of study.